Analisis Kualitas Minyak Nilam dan Faktor yang Mempengaruhi Keputusan Petani Dalam Memilih Ketel Penyulingnya - Tomi Mukhtar; Heru Prono Widayat; Yusya Abubakar (Jurnal Teknologi dan Industri Pertanian Indonesia, 2020)
Aceh Province (as one of the major producer in Indonesia) produces about 423 tons of patchouli oil yearly, harvested from about 2.041ha patchouli farm. One of problems faced by patchouli farmer is related to post-harvest handling process, especially during distillation. Many farmers still use simple distillation equipment made from used drums, so that the quality of the oil is relatively low. In the meantime, equipment made from better materials (such as stainless steel) is already available commercially, but farmer has not yet willing to adopt the technology. The aims of this study are to determine the percentage of farmers who still use the distillation unit made from used drum, analyze the yield and quality of patchouli oil at the farm level, and analyze the factors that influence the farmer decision in choosing the type of distillation unit. Respondents in this study came from three sub-districts of patchouli producers in South Aceh District. Data was collected by means of interviews, distribution of questionnaires, and observation. Patchouli oil samples were taken from farmers' patchouli distillation unit to be analyzed. The results showed that the majority of farmers still used distillation unit made from used drums (79%), while those who use stainless steel distillation unit is very small (21%). The laboratory analysis (by GC-MS) showed that the quality of patchouli oil from stainless steel distillation unit is better than patchouli oil from used-drum distillation unit. The factors that influence farmer’s decision in choosing type of distillation units are the initial investment costs and operational costs of distillation unit. Many farmers find it difficult to get enough initial capital to buy the stainless steel unit, therefore the majority of farmers choose to use used-drum distillation unit (which is cheaper) instead of stainless steel unit.